Linking Financial Development and Environment in Developed Nation Using Frequency Domain Causality Techniques: The Role of Globalization and Renewable Energy Consumption - Mosleh, Sara; Al-Geitany, Souha; Lawrence Emeagwali, Okechukwu; Altuntaş, Mehmet; Agyekum, Ephraim Bonah; Kamel, Salah; El-Naggar, Mohamed F.; Agbozo, Ebenezer (Frontiers in Environmental Science, 2022)
The topic of whether globalization, energy consumption and financial development can substantially reduce emissions during the globalization era remains unanswered. In this context, this research highlights empirical indications supporting this theoretical discord; assessing the effect of globalization, energy consumption and financial development on the CO2 emissions in Japan (utilizing a dataset that spans between 1990 and 2019). The study employed the Autoregressive Distributed Lag (ARDL) technique and frequency domain causality to probe these relationships. Unlike other conventional causality tests, the frequency domain causality test can capture causality at different frequencies. The findings from the ARDL analysis disclosed that globalization and renewable energy contribute to the mitigation of CO2 emissions while fossil fuel, economic growth and financial development caused an upsurge in CO2 in Japan. Furthermore, the frequency domain demonstrated that all the exogenous variables can forecast CO2 mostly in the long-term which implies that any policy initiated based on the exogenous variables will impact emissions of CO2. Based on the results obtained, Japan has to improve its financial systems and increase its use of renewable energy. Furthermore, Japan needs to restructure its policy regarding globalization owing to the fact that it contributes to the degradation of the environment. Since globalization is a major driver of economic growth, the government should concentrate on luring and licensing investors that use environmentally beneficial (net-zero) technology.